Effects of Sila-bac and Silo Guard on alfalfa silage quality and corn supplementation on steer performance - K. Bolsen; H. Ilg; M. Hinds (Kansas Agricultural Experiment Station Research Reports, 1981)
Inoculant (Sila-bac) and enzyme (Silo Guard) silage additives were evaluated with first-cutting alfalfa silage. Control and treated silages were made in 50-ton concrete stave silos and three types of experimental silos (nylon bags buried in the stave silos, 5-ga11on plastic containers, and 55-gallon metal drums). Each silage from the stave silos was full-fed to 16 steers in individual pens. Half the steers received 2 lbs. of supplement; the other half received supplement + 2 lbs. of cracked corn. Steers fed Sila-bac and Silo Guard silages performed slightly better than those fed control silage. Adding cracked corn improved rate of gain (.37 lb./day) and feed efficiency (.71 lb. less DM/lb. of gain). Each 1.0 lb. of extra gain required 5.5 lbs. of air-dry corn.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Sila-bec; Silo Guard; Alfalfa silage quality; Corn supplementation; Steer performance